2012
DOI: 10.1523/jneurosci.1599-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Amygdala–Cortical Functional Connectivity Predicts Social Network Size in Humans

Abstract: Using resting-state functional MRI data from two independent samples of healthy adults, we parsed the amygdala’s intrinsic connectivity into three partially-distinct large-scale networks that strongly resemble the known anatomical organization of amygdala connectivity in rodents and monkeys. Moreover, in a third independent sample, we discovered that people who fostered and maintained larger and more complex social networks not only had larger amygdala volumes, but also amygdalae with stronger intrinsic connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
266
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(291 citation statements)
references
References 105 publications
(145 reference statements)
21
266
4
Order By: Relevance
“…These findings coincide with biparental animals' greater integration of multiple brain networks (7). Both the amygdala and STS are key structures of the social brain circuitry (15,31,32). The STS plays a key role in social perception (33), and STS projections to the amygdala determine its role in mentalizing and social perception processes (28,29).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…These findings coincide with biparental animals' greater integration of multiple brain networks (7). Both the amygdala and STS are key structures of the social brain circuitry (15,31,32). The STS plays a key role in social perception (33), and STS projections to the amygdala determine its role in mentalizing and social perception processes (28,29).…”
Section: Discussionmentioning
confidence: 54%
“…The STS sends feed-forward projections to the amygdala and receives feedback projections from it (29), with the amygdala fine-tuning neural response to affect-laden stimuli (34). Stronger amygdala-STS connectivity has been linked with better social cue detection (32), and amygdala-damaged patients revealed lower STS response to affective facial expressions (35). Individuals with larger, more complex social networks showed stronger amygdala-STS connectivity, suggesting greater adeptness at initiating and maintaining social bonds (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, to examine evidence for the behavioral relevance of our findings, we tested whether coupling indices are associated with parameters of the subject's social functioning, as indexed by the average complexity of a pair's social networks. The self-report questionnaire social network index (SNI) (22) is a repeatedly used measure describing the complexity and size of the social network a subject is embedded in, and has been found to be related to neural markers such as the volume and function of socially relevant brain regions (23)(24)(25)(26). Indeed, the coupling index proved to be significantly positively associated with the mean social network complexity of real pairs (repeated measures ANOVA; F = 5.0, P = 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous studies, we chose the complexity of the social environment (22), which had been found to be related to connectivity strength within social brain networks in humans as well as to the size of a main subregion, the amygdala (23,26). Indeed, we found a relationship in the expected direction, with higher coupling related to increasing real-world social complexity.…”
Section: Discussionmentioning
confidence: 97%